Analysis of Node Router Performance with Babel and OLSR Protocol on MANET in Disaster Area - Satriawan, Kelfin Agung; Suharto, Nugroho; Mas'udia, Putri Elfa (Politeknik Negeri Malang, 2023)
Natural disasters are events caused by nature, including earthquakes, tsunamis, volcanic eruptions, droughts, hurricanes, and landslides. Natural disasters can cause telecommunications infrastructure to become damaged or malfunction. Therefore, flexible network technology is needed and does not depend on infrastructure, so that when the existing infrastructure is not functioning, humans can still communicate. One of the network technologies that is flexible and has infrastructureless characteristics, or basically does not require infrastructure, is Mobile Ad-hoc Network (MANET) technology. So that MANET technology becomes an option that can be a solution to existing problems, namely when a natural disaster occurs and the existing telecommunications infrastructure doesn't function. In the MANET network to communicate data between nodes that are far apart, it takes hops to a node in order to communicate, when a node is selected as a hop, the node will automatically act as a router node, the role of the router node is as a successor or communication liaison from a node to other nodes. In a router node, the parameters that are considered are CPU usage and RAM usage, because with increasing communication the router will process more data so it will take time to process the data, this will cause delay process. In this study, the performance of router nodes on Babel and OLSR will be discussed on the performance of router nodes on a fixed network with a stationary, moving and swapping node testing scheme. The parameters used in this study are CPU usage, RAM usage, and delay process.